Optimizing Financial Management to Enhance Curriculum Delivery and Student Development in Vocational High Schools - Novianti; Ismanto, Bambang; Trisatyawati, Sophia (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
Effective financial management is fundamental to the successful implementation of curricula and the promotion of student development in Vocational High Schools (SMK). This study explores the impact of budget planning, income and expenditure management, and financial oversight on the quality of teaching and learning outcomes. Using a qualitative research approach, the study examines how financial strategies can be aligned with educational objectives to address diverse student needs. The findings underscore the importance of transparent and accountable financial practices in facilitating inclusive education, optimizing resource allocation, and supporting innovative teaching methodologies. By strengthening financial systems, vocational schools can achieve their educational goals and prepare students for dynamic career environments.